Subclinical myocardial changes in rheumatoid arthritis: cardiovascular magnetic resonance evidence of immuno-inflammatory remodeling - Tarjanyi, Zoltan; Szabo, Liliana; Mong, Nikoletta; Mahmood, Adil; Dohy, Zsofia; Drobni, Zsofia Dora; Panajotu, Alexisz; Tothfalusi, Laszlo; Szappanos, Agnes; Raisi-Estabragh, Zahra; Merkely, Bela; Nagy, Gyorgy; et al. (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesRheumatoid arthritis (RA) is associated with increased cardiovascular (CV) risk, yet the mechanisms remain unclear. This study aimed to evaluate myocardial structure, function, and tissue characterization using cardiovascular magnetic resonance (CMR) in RA patients and explore associations with RA disease severity.MethodsThis mixed case-control study included 48 RA patients and 34 age- and sex-matched controls. RA patients were enrolled based on ACR/EULAR criteria, excluding other autoimmune diseases or significant coronary artery calcification. CMR assessed myocardial structure, function, and tissue characteristics, including native T1/T2 mapping, ventricular volumes, strain analysis, and late gadolinium enhancement. Linear regression models adjusted for age, sex, hypertension, and diabetes evaluated associations between RA characteristics and CMR parameters.ResultsRA patients exhibited elevated native T1 values (980 ± 34 ms vs. 955 ± 33 ms; P < 0.01), indicative of subclinical myocardial fibrosis. Left ventricular global longitudinal strain (GLS) was reduced (22 ± 2% vs. 24 ± 3%; P < 0.01), and increased left ventricular mass and remodeling were observed. Right ventricular end-diastolic and end-systolic volume indices were lower in RA patients (RVEDVi: 68 ± 14 ml/m2 vs. 75 ± 12 ml/m2, P = 0.02). Disease duration correlated negatively with GLS (β = −0.06, P < 0.05), while higher DAS28 scores were linked to reduced ejection fraction (β = −4.11, P < 0.05).ConclusionsThis study demonstrates significant myocardial alterations in RA patients, including fibrosis, impaired systolic function, and ventricular remodeling, linked to disease severity. These findings highlight the need for early CV risk assessment and inflammation control to mitigate CV complications in RA.